Economic Empowerment: A Case Study of Policy Formulation for a Poverty Alleviation Program in Dewa Tana Village, Central Sumba - Yuvensius Ramompas; Osfred Umbu Djadji; Pajaru Lombu; Umbu Ho Ara; Salmon Pandarangga; Erwianta Gustial Radjah; Tumpal Pangihutan Situmorang; Anastasia Hara Aji (Jurnal Abdimas, 2026)
Community economic empowerment is a strategic approach to addressing the complex, multidimensional nature of rural poverty. This study aims to analyze the policy formulation process for an economic empowerment program to alleviate poverty in Dewa Tana Village, Central Sumba Regency. The method used was community service (PkM) with a participatory approach, implemented in three stages: planning, implementation, and monitoring and evaluation. The research subjects comprised 15 participants, including village officials and community leaders. Implementation techniques included lectures, discussions, demonstrations, and a Participatory Rural Appraisal (PRA) approach using social maps, cause-and-effect diagrams, and economic seasonal calendars. The results showed an average increase in participants' understanding of 22% based on pre-test and post-test scores across policy concepts, structural factors, cultural factors, and poverty analysis. The findings also identified that the main obstacles to policy formulation include geographical, socio-cultural, and institutional factors, as well as the low quality of human resources and limited community participation. This activity resulted in a follow-up plan in the form of a policy model based on local potential and strengthening synergy between academics and the village government. This research recommendation emphasizes strengthening community participation, increasing human resource capacity, and developing sustainable programs tailored to local needs to enhance the effectiveness of poverty alleviation policies.